The Geography of Place in the Qur’anic Narrative: A Hermeneutical Study of the Story of Moses and Al-Khidr through the Lenses of Philosophical Symbolism and Pedagogical Perception - Alriteemi, Abraheem; Mowafg Masuwd; Masoud, Mohieddin; Alsayd, Abdulnasir; Aboujanah, Yousuf; Alrumayh, Safa; Ayad, Nahid (Fakultas Agama Islam, Universitas Hasyim Asy'ari, 2025)
This study offers an interpretive, semantic, and educational analysis of the story of Moses and al-Khidr in Surah al-Kahf (verses 60–82). It focuses on the symbolic and geographical dimensions of place and its role in shaping the educational and epistemological experience of Prophet Moses (peace be upon him). The research adopts an integrative approach that combines classical Qur’anic exegesis, Islamic mysticism, and theories of symbolic space in religious and philosophical thought. The story is analyzed as a sequence of transitional phases in a geographical space that goes beyond physical description, carrying spiritual and pedagogical implications. These stages include the symbolic starting point at the